2017
DOI: 10.9734/bjmcs/2017/33729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Calinski-Harabasz Criterion as Fitness Measure for Genetic Algorithm Based Segmentation of Cervical Cell Nuclei

Abstract: In this paper, the classification capability of Calinski-Harabasz criterion as an internal cluster validation measure has been evaluated for clustering-based region discrimination on cervical cells. In this approach, subregions in the sample image are initially randomly constructed to be the individuals of the population. At each generation, individuals are evaluated according to their Accordingly a novel genetic structure for meta heuristic area isolation is proposed. Evaluation of proposed combination of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The algorithm was able to detect close relationships between questions, with small between-cluster variance indicating similar clusters. The Calinski-Harabasz score [55] was 124.89, which is relatively low, indicating that the clusters were not well separated, and may not be distinct. There was a variation within the Calinski-Harabasz score when the assigned number of neighbors (n-neighbors) was between 2 and 19.…”
Section: Semantic Analysis and Manual Comparison To Standardize The C...mentioning
confidence: 96%
“…The algorithm was able to detect close relationships between questions, with small between-cluster variance indicating similar clusters. The Calinski-Harabasz score [55] was 124.89, which is relatively low, indicating that the clusters were not well separated, and may not be distinct. There was a variation within the Calinski-Harabasz score when the assigned number of neighbors (n-neighbors) was between 2 and 19.…”
Section: Semantic Analysis and Manual Comparison To Standardize The C...mentioning
confidence: 96%
“…Other works applied different CVIs, e.g., Xiao et al [ 38 ] proposed a hierarchical K-means algorithm that incorporates the Davies–Bouldin index as a metric, enabling the efficient identification of the number of clusters while minimizing computation time and costs. Caglar et al [ 39 ] showed the effectiveness of the Calinski–Harabasz index as a robust cluster validation measure; it surpassed the performance of the Jaccard index and F-score in the clustering evaluation of cervical cells. Some relevant works on human posture recognition have also employed the aforementioned CVI for both supervised and unsupervised learning techniques [ 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…This choice is also based on our analysis using two concrete statistical scores and allows us to better tune our unsupervised learning process. Two well known statistical clustering scores the (a) silhouette (S) score [50] and (b) Calinski-Harabasz (CH) score [51] were used for choosing the optimization parameter k for all data sets. These have been chosen based on their high intrinsic differences.…”
Section: Clustering and Optimizationmentioning
confidence: 99%